Stress state and failure path of a tension tower in a transmission line under multiple loading conditions. (December 2020) - Fu, Xing; Du, Wen-Long; Li, Hong-Nan; Li, Gang; Dong, Zhi-Qian; Yang, Li-Dong
Abstract: As important components of transmission tower-line systems, tension towers are used mainly at the corner of the line or among several suspension towers to prevent their progressive collapse under extreme loading conditions. Compared with suspension towers, tension towers exhibit more complicated stress states and different failure patterns. Under the activities of various disasters, the failure of tension towers will result in more serious consequences, but their failure mechanism is seldom investigated. In this paper, the stress and displacement distributions of a tension tower under eight different loading cases are analyzed based on a full-scale test. The test tower successfully passes a 100% loading step test under the first seven loading cases and is overloaded to collapse under Case 8. Then, the finite element model (FEM) of the test tower is established, and the buckling instability of members is simulated by applying initial imperfections. The calculated critical loading level and member strains are in good agreement with the full-scale test results, verifying the reliability of the FEM and analysis method. Finally, the pushover analysis is performed to simulate the failure pattern of the tension tower, and the results demonstrate that the failure mode is the shear failure. Plastic failure occurs firstly in the diagonal members of the cross arm under compression, after which the main members yield quickly, completely forfeiting the bearing capacity of the tower. For the tension tower employed in this test, the diagonal members under compression play a decisive role in the ultimate bearing capacity. Highlights: The upper diagonal members are the initial failure positions, accelerating the buckling of the lower diagonal members. The numerical simulation confirms that the FEM and analysis method are reliable by comparing with the full-scale test. FEM has the advantage of providing every detail of tower response, capturing the plastic deformation and bearing capacity. In design stage for a tension tower, the diagonal member of the cross arm is one of the critical positions.